Synaptic transmission and fokker-planck equation - Filho, Elso Drigo [UNESP]; Araujo, Marcelo T. [UNESP] (My University, 2012)
An important neurologic process consists in a time dependent transmission of the electric signal between neurons. The description of such signal is the objective of this work. In this way, the Fokker-Planck equation with a term of control which depends on time is used. The applied force is characterized by the existence of a barrier that increases with time and reduces the diffusion of particles. The solution of the equation is obtained by an ansatz that satisfies the initial conditions of the problem. Numerical examples of the time evolution of the found solutions are analyzed by calculating the escape rate and the time necessary to across the barrier for different values of diffusion constant.
Keywords: Escape rate; Fokker-Planck equation; Synaptic transmission